Implementasi Manajemen Pembiayaan dan Sarana Prasarana Untuk Meningkatkan Kualitas Pembelajaran - Ratna Indrasari; Suherman; Cucu Atikah (Program Studi Manajemen Pendidikan, 2023)
This study aims to describe the implementation of financing management and infrastructure to improve the quality of learning at SMA Negeri 1 Kramatwatu, Serang Regency. The method used in this research is qualitative. The results of the study show that the implementation of financing management and infrastructure is an integral part in efforts to improve the quality of learning. Implementation of management of financing and infrastructure in SMA Negeri 1 Kramatwatu has gone through managerial stages, namely planning, implementation and supervision (auditing and accountability). Budget execution activities include recording income and expenses in the ARKAS system and preparing accountability reports in the form of notes, receipts, and activity documentation. The implementation phase of the implementation of infrastructure includes the procurement and arrangement of school facilities. The supervision stage for the implementation of financing management and infrastructure is carried out by internal schools and external parties which includes monitoring activities evaluating the acquisition of assets and consumables with BOS funding sources, BOS realization reports and cash opname.